2022
DOI: 10.1038/s41392-021-00870-3
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of RAS/MAPK pathway confers MCL-1 mediated acquired resistance to BCL-2 inhibitor venetoclax in acute myeloid leukemia

Abstract: Despite high initial response rates, acute myeloid leukemia (AML) treated with the BCL-2–selective inhibitor venetoclax (VEN) alone or in combinations commonly acquires resistance. We performed gene/protein expression, metabolomic and methylation analyses of isogenic AML cell lines sensitive or resistant to VEN, and identified the activation of RAS/MAPK pathway, leading to increased stability and higher levels of MCL-1 protein, as a major acquired mechanism of VEN resistance. MCL-1 sustained survival and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 50 publications
6
56
1
Order By: Relevance
“…Studies have shown that the total level of mitogen-activated protein kinase (MAPK) in TP53 mutant cells is increased. The MAPK signalling pathway is involved in the regulation of cell proliferation and apoptosis and can increase the expression of MCL-1 protein, thereby increasing the competitive binding of MCL-1 and BCL-2 to venetoclax and thus affecting venetoclax-mediated cell apoptosis [ 45 , 58 61 ]. Further studies have shown that the expression level of BCL-XL was increased and the levels of PMAIP1 (NOXA), PUMA and BAK were decreased in a TP53 knockout cell line with reduced sensitivity to venetoclax, which caused inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the total level of mitogen-activated protein kinase (MAPK) in TP53 mutant cells is increased. The MAPK signalling pathway is involved in the regulation of cell proliferation and apoptosis and can increase the expression of MCL-1 protein, thereby increasing the competitive binding of MCL-1 and BCL-2 to venetoclax and thus affecting venetoclax-mediated cell apoptosis [ 45 , 58 61 ]. Further studies have shown that the expression level of BCL-XL was increased and the levels of PMAIP1 (NOXA), PUMA and BAK were decreased in a TP53 knockout cell line with reduced sensitivity to venetoclax, which caused inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In AML patients that progress or relapse after treatment with venetoclax and azacitidine, 27% of the patients had a N/KRAS mutation, and 22% a PTPN11 mutation [ 32 , 95 ], suggesting that these mutations are more frequently present in refractory or relapsed disease. The reduced sensitivity to venetoclax in RAS- and PTPN11-mutated AML patients can be explained by the activation of the RAS/MAPK signaling pathway [ 96 ], allowing the AML cells in RAS- and PTPN11-mutated cases to use multiple sources of energy for cell survival, including fatty acid and amino acid metabolism, glycolysis and upregulation of OXPHOS [ 97 , 98 ]. Moreover, AML with a PTPN11 mutation often has a more monocytic cell type [ 99 ], which generally has increased dependency on MCL-1 instead of BCL-2 [ 100 ], thereby decreasing the efficacy of venetoclax.…”
Section: Aml Patients With Mutations In Flt3 Tp53 and Ras Showed Redu...mentioning
confidence: 99%
“…In some AML patients, leukemic cell survival depends on other functional anti-apoptotic proteins than BCL-2, for example MCL-1 ( Figure 1 B) [ 119 ]. These patients may have primary resistance to venetoclax-based therapies due to the upregulation of MCL-1, which is stabilized through epigenetic modifications caused by the activation of the RAS/MAPK signaling pathway [ 96 , 111 ]. As previously mentioned, AML cells with a more monocytic AML cell type or the FLT3, RAS, PTPN11 or TP53 mutations have increased dependency on MCL-1 instead of on BCL-2 [ 90 , 100 , 101 , 110 , 120 ].…”
Section: Mechanisms Determining Sensitivity Of Aml To Venetoclaxmentioning
confidence: 99%
See 2 more Smart Citations